c-jun N-terminal kinase is involved in AUUUA-mediated interleukin-3 mRNA turnover in mast cells. - Ming, X F (1998)
Whereas signalling pathways involved in transcriptional control have been studied extensively, the pathways regulating mRNA turnover remain poorly understood. We are interested in the role of mRNA stability in cell activation and oncogenesis using PB-3c mast cells as a model system. In these cells the short-lived interleukin-3 (IL-3) mRNA is stabilized by ionomycin treatment and following oncogenesis. To identify the signalling pathways involved in these mechanisms, we analysed the effect of different kinase inhibitors. SB202190 and wortmannin were shown to antagonize ionomycin-induced IL-3 mRNA stabilization in PB-3c cells in the presence of actinomycin D, and this effect coincided with their ability to inhibit c-jun N-terminal kinase (JNK) activation by ionomycin. Moreover, transfection of activated MEKK1 amplified ionomycin-induced IL-3 mRNA expression at the post-transcriptional level, and a dominant-negative mutant of JNK counteracted mRNA stabilization by ionomycin. Taken together, these data indicate that JNK is involved in the regulation of IL-3 mRNA turnover in mast cells. In addition, transfection experiments revealed that the cis-acting AU-rich element in the 3' untranslated region of IL-3 mRNA is necessary and sufficient to confer JNK-dependent mRNA stabilization in response to cell activation.